Herbage availability, chemical composition and dry matter intake in mixed pasture of Brachiaria decumbens with Stylosanthes guianensis - Aroeira, Luiz Januário Magalhães; Paciullo, Domingos Sávio Campos; Lopes, Fernando César Ferraz; Morez, Milton José Frota; Saliba, Eloísa Simões; Silva, Janaína Januário da; Ducatti, Carlos (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the herbage availability, nutritive value, dry matter intake and grass and legume percentage in diet of crossbred Holstein-Zebu cows, in pasture with Brachiaria decumbens cv. Basilisk, Stylosanthes guianensis var. vulgaris cv. Mineirão and tree legumes. To estimate the fecal output, it was used 10 g cow-1 day-1 of chromium oxide during ten consecutive days. Extrusa samples were used to determine the chemical composition and in vitro dry matter digestibility. B. decumbens availability varied with climatic conditions, while S. guianensis availability decreased linearly along the experimental period. Dry matter intake was higher in May/2001 (1.9% body weight) and did not differ among other months (1.5% body weight). Low dry matter intake values were related to low in vitro dry matter digestibility coefficients (42.1% to 48.0%) and high neutral detergent fiber content (70.2% to 79.4%). Dry matter intake was directly related to legume percentage in the pasture. This observation could indicate the potential of mixed pasture for improving nutritive value in dairy cattle diet.